The Effectiveness of the Intensive English for Islamic Studies Program at STAIN Jember - Ninuk Indrayani (Fenomena, 2012)
STAIN Jember provides an English Program for Islamic Studies to first-semester students. This program is managed by the Language Unit (UPB) of STAIN Jember with 0 credit points, where students can learn the four basic English skills: Listening, Speaking, Reading, and Writing, as well as three fundamental components: Vocabulary, Pronunciation, and English Grammar. This research is evaluative in nature. Using research instruments such as interviews with Intensive English lecturers and administrative staff, student questionnaires, and documentation of student entrance exam scores, the researcher aims to evaluate the effectiveness of the English Program for Islamic Studies. STAIN Jember memberikan Program Bahasa Inggris dalam Pembelajaran Islam kepada mahasiswa yang berada pada semester pertama. Program tersebut dikelola oleh UPB (Unit Pusat Bahasa) STAIN Jember dengan memiliki 0 kredit, di mana mahasiswa dapat belajar tentang empat keterampilan dasar bahasa Inggris: Mendengarkan, Berbicara, Membaca, dan Menulis, serta tiga komponen dasar, yaitu: Kosakata, Pengucapan, dan Tata Bahasa Inggris. Penelitian ini adalah penelitian evaluatif. Dengan menggunakan instrumen penelitian yang meliputi: wawancara dengan dosen pengajar Bahasa Inggris Intensif dan staf administrasi, angket kepada mahasiswa, dan dokumentasi nilai ujian masuk mahasiswa, peneliti mencoba untuk mengetahui keefektifan dari Program Bahasa Inggris dalam Pembelajaran Islam.